Meat and Bone Characteristics of Broiler Chickens Fed Groundnut Cake-Based Diets as Affected by Graded Dietary Supplements of Crystalline L- Lysine and DL- Methionine (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
Effects of supplemental dietary lysine and methionine in a Groundnut Cake (GNC) based diets on meat and bone characteristics of broiler chickens were investigated. In a completely randomized design, a total of 168 one - day – old Arbor acre broiler chicks were randomly allocated to seven dietary treatments each in triplicate of eight birds per replicate. The Seven starter and finishers’ diets were: GNC based diets without any amino acid (lysine or methionine) supplementation (T1); GNC diet + 0.2% lysine (T2); GNC diet + 0.4% lysine (T3); GNC diet + 0.2% methionine (T4); GNC diet + 0.4% methionine (T5); GNC diet + 0.2 lysine and 0.2% methionine (T6) and GNC diet + 0.4% lysine and 0.4% methionine (T7). Experimental diets and water were offered to birds ad libitum in an experiment lasting six-week. At day 42, two birds per replicate were slaughtered, meat and bone characteristics determined. There were significant variations (P